Making and Understanding Analytic Geometry using the software Geogebra - Berti, Juliana Pereira; Sauer, Laurete Teresinha Zanol (Scientia cum Industria, 2016)
Mathematics Education has been undergoing transformations, especially with regard to the new requirements contained in legal documents. The various forms of expression language of mathematics and the use of technological resources are some of the suggestions of the National Curriculum Guidelines for Secondary Education. Thus, analytic geometry as a curricular component of mathematics also goes through these adjustments. In order to create alternatives to work that content and, thinking of the subject-object interaction, it developed a short course that uses the Dynamic Geometry through the GeoGebra software, as facilitator of the knowledge construction process. The methodology has seven activities. Are activities aimed at the line of study, including its equations and the relative position of the lines in the plan; the study of the circumference and the relative position of two circles in the plane; and the geometric interpretation of the ellipse, the parabola and hyperbole. We hope, therefore, provide educators strategies to reflect and rebuild their practices in math classes in high school. http://dx.doi.org/10.18226/23185279.v3iss3p120